An experimental study on hole quality and different delamination approaches in the drilling of CARALL, a new FML composite - Ekici Ergün (University of Belgrade - Faculty of Mechanical Engineering, Belgrade, 2021)
In this study, the hole quality was investigated in the drilling of CARALL composite. In addition, the delamination factor calculation approaches of Chen, Davim, and Machado were compared in terms of the delamination damage at the hole entrance surface. Chen's approach is based on the conventional delamination factor (F d) and Davim's on the adjusted delamination factor (F da). Finally, Machado's approach is based on the minimum delamination factor (F min). The values closest to the nominal hole diameter value were obtained with the uncoated (T1), followed by the TiN-TiAlN-coated (T2) and TiAl/TiAlSiMoCr-coated (T3) carbide drills, respectively. The average circularity error values for the hole top and bottom surfaces were 6.184 µm, 7.647 µm, and 8.959 µm for T1, T2, and T3 tools, respectively. Delamination factor values varied between 1.174 and 1.804. The F da values were found to be the highest, followed by F d values, with F dmin values determined as the lowest.